EFFICACY OF COMBINED THERAPY IN CHILDREN WITH HIV INFECTION - E.N. Simovan'yan; V.B. Denisenko (Union of pediatricians of Russia, 2010)
To achieve a sustainable virus replication suppression, positive dynamics in clinical and immunologic metrics of children with HIV infection, it is necessary to use the most efficient, safe and convenient patterns of highly active antiretroviral therapy. Examined were 25 children with HIV infection aged 12 to 15 years who were administered non nucleoside reverse transcriptase HIV inhibitor, nevirapine in combination with two nucleoside reverse transcriptase inhibitors - zidovudine/lamivudine. The pattern involving combined therapy was characterized by higher clinical and laboratory efficacy, no side effects, convenience of administration, which makes it a preferred choice for using in children with HIV infection at ages above 12.Key words: HIV infection, children, zidovudine, lamivudine. (Pediatric Pharmacology. - 2010; 7(2):41-45)